The Paris seamstress - Lester, Natasha, 1973- (Forever, 2018)
1940: As the Germans advance upon Paris, young seamstress Estella Bissette is forced to flee everything she's ever known. She's bound for New York City with her signature gold dress, a few francs, and a dream: to make her mark on the world of fashion. Present day: Fabienne Bissette journeys to the Met's annual gala for an exhibit featuring the work of her ailing grandmother - a legend of women's fashion design. But as Fabienne begins to learn more about her beloved grandmother's past, she uncovers a story of tragedy, heartbreak and family secrets that will dramatically change her own life.